Synthesis of lanthanum-modified clay soil-based adsorbent for the fluoride removal from an aqueous solution and groundwater through batch and column process: mechanism and kinetics - Bhan C.; Singh J.; Sharma Y.C.; Koduru J.R. (My University, 2025)
In the present work, pond clay was modified with lanthanum and applied for fluoride uptake from an aqueous environment. The clay soil was treated with a 0.1 M solution of lanthanum oxide and heated at 500 ℃ for 90 min in a muffle furnace. The modified clay was characterized by the following techniques: particle size analysis, zeta potential, Fourier-transform infrared, scanning electron microscopy, transmission electron microscopy, pH at the zero point of charge, X-ray diffraction, Brunauer–Emmett–Teller, and X-ray photoelectron spectroscopy. The adsorption experiments revealed that modified clay soil was very effective in removing fluoride with an adsorption capacity of 1.96 mg/g. The fluoride removal was followed well with Langmuir isotherm (R2 = 0.999), pseudo-second-order kinetics (R2 = 1), and the adsorption was an exothermic process. The performance of lanthanum-modified clay (LMC) in a fixed bed column was evaluated using different models, including the Thomas, Adams–Bohart, Yoon–Nelson, and Clark models. A regeneration study was compared with NaOH and NaHCO3 and successfully performed for four adsorption cycles. A probable mechanism is proposed including ligand exchange, electrostatic attraction, and inner complexation for fluoride adsorption on the LMC. The developed adsorbent was also tested for the treatment of natural groundwater. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.